Fake News in Hate Speech Containing Ethnicities, Religions, Races and Intergroup (SARA) on Indonesian Social Media: A Forensic Linguistics Study - Agus Syahid; Sutarman Sutarman; Ana Rahmatyar; Dita Meldina; Deshinta Arrova Dewi (Anglophile Journal, 2026)
This study investigates the dissemination of fake news embedded in hate speech containing ethnicity, religion, race, and intergroup (SARA) issues on Indonesian social media from a forensic linguistic perspective. Drawing on speech act theory, the study aims to identify the linguistic forms used in the dissemination of fake news and examine their legal implications. A qualitative method with a forensic linguistic approach was employed. The data consisted of linguistic evidence extracted from eight court cases adjudicated between 2018 and 2020 and obtained from final and legally binding district court decisions available through the Supreme Court Decision Directory of the Republic of Indonesia. Data were analyzed using Searle’s speech act framework, focusing on assertive speech acts. The findings reveal two dominant forms of assertive speech acts in the dissemination of fake news, namely assertive accusations (or slander) and assertive lies. These speech acts were used to promote hate speech, blasphemy, incitement of hatred, and the humiliation or denigration of particular groups based on SARA identities. The study further demonstrates that the dissemination of fake news containing SARA-related hate speech carries significant legal consequences, as perpetrators may be prosecuted under Article 28(2) in conjunction with Article 45A(2) of Law No. 19 of 2016 concerning Electronic Information and Transactions (ITE). The findings contribute to the development of forensic linguistic scholarship by highlighting the relationship between language, misinformation, hate speech, and legal accountability in digital communication.